Hyperbolic discounting and positive optimal inflation - Liam Graham; Dennis J. Snower (Institute for the Study of Labor (IZA), 2011)
The Friedman rule states that steady-state welfare is maximized when there is deflation at the real rate of interest. Recent work by Khan et al (2003) uses a richer model but still finds deflation optimal. In an otherwise standard new Keynesian model we show that, if households have hyperbolic discounting, small positive rates of inflation can be optimal. In our baseline calibration, the optimal rate of inflation is 2.1% and remains positive across a wide range of calibrations.
urn:nbn:de:101:1-201105173304
Keywords: E20; E40; E50; 330; optimal monetary policy; inflation targeting; unemployment; Phillips curve; nominal inertia; monetary policy